1974
DOI: 10.2134/agronj1974.00021962006600050026x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium on the Incidence of Diaporthe sojae in Soybean1

Abstract: Many varieties of soybean (Glycine max (L.) Merrill) are highly susceptible to the fungus Diaporthe sojae Lehman when grown in Delaware. It has been shown, in Iowa, that potassium levels in upper pods of soybean plants decreased markedly in late season. Because the upper pods frequently had the highest incidence of D. sojae in Delaware and the infection occurs in late season, the relationship of K in soybean to the incidence of disease caused by D. sojae was studied. Two varieties of soybeans were grown in alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Sale and Campbell (1987) reported individual seed weight might increase under moderate K deficiency but was clearly decreased by severe K deficiency. Soybean seed quality issues have been associated with K deficiency on several instances (Crittenden and Svec, 1974; Camper and Lutz, 1977; Jeffers et al, 1982; Vyn et al, 2002). The literature suggests that individual seed weight reduction from K deficiency may occur and contribute to yield loss.…”
Section: Resultsmentioning
confidence: 99%
“…Sale and Campbell (1987) reported individual seed weight might increase under moderate K deficiency but was clearly decreased by severe K deficiency. Soybean seed quality issues have been associated with K deficiency on several instances (Crittenden and Svec, 1974; Camper and Lutz, 1977; Jeffers et al, 1982; Vyn et al, 2002). The literature suggests that individual seed weight reduction from K deficiency may occur and contribute to yield loss.…”
Section: Resultsmentioning
confidence: 99%
“…Phytomonas stewarti in sweet corn (6), tomato internal browning (7), Fusarium wilts in clover (8), and recently, gray-moldy seed in soybean (9). The previous soybean study (9) used plants grown with a soil zone partially restricted laterally in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study (Svec et al, 1976), however, potassium level was much higher in the soil prior to fertilizer application than in the study by Crittenden and Svec (1974). These findings (Crittenden and Svec, 1974) infection, as determined by agar plating, only in soils in which the potash level was so low that plants showed foliar symptoms of potassium deficiency.…”
Section: Agronomic Aspectsmentioning
confidence: 59%
“…The effect of soil potash level on phomopsis seed infection is also controversial. Crittenden and Svec (1974), Mascarenhas et al (1976), and Jeffers and Schmitthenner (1976) reported decreases in numbers of visible moldy seed with increased potassium fertilizer level, but Svec et al (1976) reported no benefit in adding potassium fertilizer. In the latter study (Svec et al, 1976), however, potassium level was much higher in the soil prior to fertilizer application than in the study by Crittenden and Svec (1974).…”
Section: Agronomic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation